Case report: Treatment with Pien-Tze-Huang for prolonged positive SARS-CoV-2 test results in COVID-19 patients: A report of five cases - Zheng, Yujiao; Cheng, Jinbo; Gu, Chengjuan; Xiao, Mingzhong; Shao, Zuoyu; Zhao, Linhua; Tong, Xiaolin (Frontiers in Medicine, 2022)
Coronavirus disease 2019 (COVID-19) has rapidly spread around the world since December 2019, becoming a global pandemic. Atypical cases of COVID-19, manifesting as prolonged positive SARS-CoV-2 test results during the convalescence period, have been encountered. These cases increase the difficulty of COVID-19 prevention and treatment. Here, we report five cases of COVID-19 patients who demonstrated prolonged positive SARS-CoV-2 tests after regular traditional Chinese medicine and western medicine treatments. After administration of Pien-Tze-Huang and cessation of previous treatments, SARS-CoV-2 tests results of the patients turned and remained negative. We believe the finding will contribute to a better understanding of atypical COVID-19 cases and hope to offer a potential therapy. Since this is a preliminary case series, larger-scale clinical trials are warranted.